Development of Image Series Media in Text Descriptive to Improve English Speaking Skills - Ernaeni Ernaeni; Herpratiwi Herpratiwi; Muhammad Sukirlan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Speaking skills are seen as a very important skill to be understood by learners of a language. This is related to the function of language as a means of communication which requires its users to be able to use the language in real communication. The implication of this is that teachers should be able to create a learning environment that is able to facilitate learners to practice functional expressions actively and communicatively. Meanwhile, speaking skill is considered as one of the language skills that is used as a benchmark in determining the quality of ability. This research uses the method of methods (SLR). regarding research methods: "Literature" which means it is a critical analysis of the research that is being done on a special topic or in the form of a question to a part of science. helps us in compiling a framework that is in accordance with the theory, findings, and results of previous research in solving the problem formulation in the research that we make. The SLR method is used to identify, review, evaluate and interpret all available research with the topic area of the phenomenon of interest, with specific relevant research questions. With the use of the SLR Method, a systematic review and identification of journals can be carried out. The results of the study are described basically the ability to speak can be influenced by the methods and media provided, the initial stimulus carried out by the teacher will be able to stimulate the child's ability, especially at the psychomotor level, interesting learning media will certainly have an influence on students during the teaching and learning process in the classroom. For this reason, the role of the teacher as a facilitator is expected in providing stimulus to students.